2020
DOI: 10.14710/dijb.3.1.2020.47-54
|View full text |Cite
|
Sign up to set email alerts
|

Study of impulse buying on Instagram users in Indonesia

Abstract: Our paper is aimed to find out the effect of online advertisement content, electronic word of mouth (e-WOM) and hedonic shopping motives on impulse buying of Indonesian users in Indonesia. Multiple linier regression analysis is used to examine the magnitude of independent variables effect which are online advertisement content, e-WOM  and hedonic shopping motives on impulse buying on instagram user in Indonesia. The analysis on 75 respondents showed that all independent variables have positive and significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
2
4
0
4
Order By: Relevance
“…Park et al (2012) study showed hedonic browsers moderates price attributes to online impulsive buying behavior. Similar study by Astuti et al (2020) showed significances between promotion and online impulsive buying behavior. It is known that marketers are trying to gain consumer's loyalty by keeping consumers satisfaction which later provokes their impulsivity on the same website in the future.…”
Section: Impulsivesupporting
confidence: 65%
“…Park et al (2012) study showed hedonic browsers moderates price attributes to online impulsive buying behavior. Similar study by Astuti et al (2020) showed significances between promotion and online impulsive buying behavior. It is known that marketers are trying to gain consumer's loyalty by keeping consumers satisfaction which later provokes their impulsivity on the same website in the future.…”
Section: Impulsivesupporting
confidence: 65%
“…Interaksi di media sosial memungkinkan terjadi pertukaran informasi mengenai produk antar konsumen. E-WOM yang berisikan pernyataan positif atau negatif sering dijadikan pertimbangan bagi konsumen untuk melakukan pembelian produk (Hennig-Thurau et al, 2004dalam Kunja & GVRK, 2018 Penelitian Astuti et al (2020) menyimpulkan bahwa e-WOM berpengaruh signifikan terhadap Impulsive Buying, dimana konsumen yang cenderung memberikan pendapat akan memberikan pengaruh yang signifikan terhadap perilaku dan kebiasaan konsumen lainnya termasuk mendorong peningkatan perilaku pembelian produk yang tidak direncanakan sebelumnya.…”
Section: Hipotesisunclassified
“…Lebih lanjut e-WOM mengarah pada pencarian opini dan pengalaman dari konsumen sebelumnya untuk mengurangi risiko mendapatkan produk yang tidak sesuai dengan harapan (Husnain et al, 2016). Astuti et al (2020) juga menyimpulkan bahwa e-WOM berpengaruh signifikan terhadap Impulsive Buying. E-WOM yang ditandai dengan adanya kegiatan berbagi pengalaman, opini kepada orang lain melalui aktifitas berbagi tautan, video, atau foto menjadi hal yang sangat penting dalam mendukung aktifitas pembelian impulsif (Astuti et al, 2020).…”
Section: B Pembahasan Pengaruh E-wom Terhadap Impulsive Buyingunclassified
See 1 more Smart Citation
“…E-WOM is a form of development from the previous theory, namely WOM (word-ofmouth) following current marketing developments which have begun to switch to electronic media (Goyette et al, 2010). Research conducted by Astuti et al, (2020) found that electronic word-of-mouth influences impulsive online buying. Kotler & Keller (2016) define sales promotion as various short-term incentives to urge the desire to buy or try a product or service.…”
Section: Electronic Word-of-mouthmentioning
confidence: 99%